What Can Agile Methods Bring to High-Integrity Software Development? Considering the issues and opportunities raised by Agile practices in the development of high-integrity software. - Chapman, Roderick; White, Neil; Woodcock, Jim (Communications of the ACM, 2017)
The authors present their views concerning the opportunities posed and potential difficulties with the concept of Agile engineering for software development. It discusses the roots of Agile engineering, Agile assumptions, and what is referred to as the Sprint pipeline. It also discusses embedded systems, high-integrity practices that can complement Agile, and continuous integration that can maintain profitability for corporations.